Pulmonary inflammatory myofibroblastic tumor and IgG4-related inflammatory pseudotumor: a diagnostic dilemma. - Bhagat, Priyanka; Bal, Amanjit; Das, Ashim; Singh, Navneet; Singh, Harkant (Virchows Archiv: European Journal of Pathology, 2013)
IgG4-related inflammatory pseudotumor (IPT) and inflammatory myofibroblastic tumor (IMT) share morphological features like a prominent fibroblastic/myofibroblastic proliferation and the presence of inflammatory cells. Since IPT is managed conservatively and IMT is treated by surgical excision, it is important to differentiate these two lesions. The aim of this study is to highlight morphological and immunohistochemical features that distinguish IPT and IMT. Clinicopathological characteristics of cases diagnosed as pulmonary IPT or IMT from 1997 to 2013 were reviewed. The histological features were studied on hematoxylin and eosin-stained sections. Immunohistochemistry was done for IgG, IgG4, ALK-1, SMA, desmin, and CD34 for classification into IPT and IMT. Of the ten patients, seven were male and the age ranged from 4 to 58 years. The tumor size ranged from 1.5 to 4.0 cm in diameter. Histologically, proliferation of bland-looking spindle cells along with fibrosis and an inflammatory infiltrate comprising of lymphocytes and plasma cells were the common morphological features of both lesions. The spindle cell proliferation was more marked in IMT whereas lymphoplasmacytic infiltrate was more prominent in IPT. Obstructive phlebitis was observed only in cases of IPT. IgG4 expression was noted in IPT, and the number of IgG4-positive plasma cells and the ratio of IgG4+/IgG+ plasma cells were significantly lower in IMT than in IgG4-related IPT. Expression of anaplastic lymphoma kinase (ALK) was observed only in IMT, but not in IgG4-related IPT. The proportion of proliferating spindle cells, lymphoplasmacytic infiltrate, obstructive phlebitis, IgG4+ plasma cells and the ratio of IgG4+/IgG+ plasma cells, and ALK expression are helpful in differentiating these morphologically similar but biologically different lesions, which require different treatment modalities.